2015
DOI: 10.1016/j.carbon.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a zeolite-templated carbon by electrochemical quartz crystal microbalance and in situ Raman spectroscopy

Abstract: Electrochemical quartz crystal microbalance was used to monitor the mass changes during the electrochemical characterization of a zeolite-templated carbon (ZTC) in 1 M H 2 SO 4 medium. Under electrochemical oxidation conditions, a high anodic current and a net mass increase were recorded, resulting in the increase of the specific capacitance owing to the contribution of the pseudocapacitance, mainly derived from the hydroquinone-quinone redox couple. Under more severe electrochemical conditions, a net mass los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…6). Therefore, it can be concluded that not all the CO-type surface oxygen groups that are formed during the electrochemical functionalization of ZTC are electroactive, in agreement with previous observations [39], and that most of the electroactive oxygen groups are still present after functionalization with ABA molecules, thus suggesting that overoxidation of the carbon material can be avoided when ABA monomers are added during the treatment. This opens the possibility of increasing the selectivity towards the most electroactive surface functional groups.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 87%
“…6). Therefore, it can be concluded that not all the CO-type surface oxygen groups that are formed during the electrochemical functionalization of ZTC are electroactive, in agreement with previous observations [39], and that most of the electroactive oxygen groups are still present after functionalization with ABA molecules, thus suggesting that overoxidation of the carbon material can be avoided when ABA monomers are added during the treatment. This opens the possibility of increasing the selectivity towards the most electroactive surface functional groups.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 87%
“…In addition, the Raman spectra exhibited no significant difference in the intensity ratio of the D- and G-bands or the band broadness for the carbon samples obtained using the different synthesis conditions because zeolite-templated carbons normally show a very broad intrinsic D-band that is attributed to the presence of five- or seven-membered carbon rings in the curved carbon structure (Supplementary Fig. 2 ) 3 , 13 , 23 , 24 .…”
Section: Resultsmentioning
confidence: 99%
“…This band is associated to a lattice vibration analogous to that of the G band but involving graphene layers which are not directly sandwiched between two other graphene layers (i.e. 'boundary layer planes') [28][29][30][31] . Samples treated at 1100 and 1200 ºC have similar Raman spectra.…”
Section: Advanced Catalysts For Oxygen Reduction Reaction Based On Ndmentioning
confidence: 99%